Strategy Management of the Art for Children (AFC) Program 2025 as a Non-Formal Arts Education at Taman Budaya Yogyakarta - Nabila Yola Insani; Rr Vegasari Adya Ratna; Dian Ajeng Kirana (Institut Seni Indonesia Yogyakarta, 2026)
This research was motivated by the existence of Art for Children (AFC) Taman Budaya Yogyakarta (TBY), which for more than two decades has provided non-formal art education for children. This study describes the strategic management applied in the management of the AFC TBY program through the application of management functions and three important stages in strategic management. The management functions used refer to the POSDCORB theory, which has been simplified to PODR (planning, organizing, directing/actuating, and reporting) to suit the characteristics of the AFC TBY program. The three stages of strategic management include strategy formulation through SWOT analysis, strategy implementation through the application of AFC TBY program policies, and strategy evaluation through assessment of the strategies implemented.This study aims to analyze the application of management functions and strategic management in non-formal arts education at AFC TBY. The method used is descriptive qualitative with data collection techniques in the form of interviews with human resources who are directly involved, non-participatory observation, and documentation of AFC TBY activities obtained from news archives and records stored at the Yogyakarta Cultural Park Library. Accordingly, this research is expected to contribute to the development of programs that are responsive to issues arising from both internal and external factors, while also maintaining AFC TBY’s role as an inclusive and sustainable non-formal art education space.